Rediscovery of Arrabidaea chica (Bignoniaceae) and Entada polystachya var. polyphylla (Fabaceae) in Puerto Rico - Caraballo-Ortiz, Marcos A. (Phytotaxa, 2013)
In this contribution the rediscovery of the lianas Arrabidaea chica (Bignoniaceae) and Entada polystachya var. polyphylla (Fabaceae-Mimosoideae) in Puerto Rico is reported. These species were first collected during the 1880s and subsequently considered extirpated. Their current status in Puerto Rico is discussed, and recommendations for their conservation are offered.